Competition demystified a radically simplified approach to business strategy - Greenwald, Bruce C. (New York Portfolio, 2005)
Bruce Greenwald, one of the nation?s leading business professors, presents a new and simplified approach to strategy that cuts through much of the fog that has surrounded the subject. Based on his hugely popular course at Columbia Business School, Greenwald and his coauthor, Judd Kahn, offer an easy-to-follow method for understanding the competitive structure of your industry and developing an appropriate strategy for your specific position.
Includes bibliographical references (p. 379-383) and index.
Keywords: Strategic planning